Analysis of structure of a public debt of the countries of Latin America - F. A. Ahmed Abu Bakr (Vestnik MGIMO-Universiteta)
The article addresses the problem of public debt restructuring in seven largest countries of Latin America. Over the last decade there has been a steady decline in nations’ external debt liabilities. This process was originated by two main contributors: worsening borrowing conditions on the world credit market, encouraging governments to deleverage their external credit position, and a solid financial standing underpinned by a positive external environment. It is LAC-7 countries’ strong fiscal position that propelled the development of national debt market and attracted international investors. But as the present report reveals international capital inflows into public debt market is highly volatile, concentrated in the short term segment and insufficient to finance constantly rising needs of the emerging nations. Finally, the author considers debt management options for local government policies weighing the implications of the ongoing global financial crisis and the scarcity of external credit resources